Proceedings of the VII European Congress on Computational Methods in Applied Sciences and Engineering (ECCOMAS Congress 2016) 2016
DOI: 10.7712/100016.1998.11192
|View full text |Cite
|
Sign up to set email alerts
|

A New Shell Finite Element With Drilling Degrees of Freedom and Its Relation to Existing Formulations

Abstract: This contribution deals with shell element formulations involving three rotational degrees of freedom. Its purpose is twofold. Firstly, a review of relevant non-linear shell theories as well as finite element implementations is given and corresponding defects are addressed. Secondly, a geometrically linear shell element formulation is presented which is free of any of these defects. Conventional shell theories involve two rotational degrees of freedom, the drilling rotation being excluded. Three standard metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Recently, some advances have been reported that reduced or eliminated the dependence of the solution on the drilling stiffness parameters. 12,22 The second, global approach attempts to treat the drilling degrees of freedom in the assembled system of equations. 24 One possibility is to introduce constraints applied to singular degrees of freedom upon detection of zero pivots.…”
Section: Handling Of the Drilling Rotationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, some advances have been reported that reduced or eliminated the dependence of the solution on the drilling stiffness parameters. 12,22 The second, global approach attempts to treat the drilling degrees of freedom in the assembled system of equations. 24 One possibility is to introduce constraints applied to singular degrees of freedom upon detection of zero pivots.…”
Section: Handling Of the Drilling Rotationsmentioning
confidence: 99%
“…On the other hand, too small of a drilling stiffness would destroy the condition number of the stiffness matrix. Recently, some advances have been reported that reduced or eliminated the dependence of the solution on the drilling stiffness parameters 12,22 …”
Section: Handling Of the Drilling Rotationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this example, the acting load gives rise to in-plane bending and extensive shear deformation. The solutions for the vertical displacement at the point A (u A ) are normalized with the reference solution u ref ¼ 23:91 provided by Winkler and Plakomytis [43] and listed in Table 5. Obviously, the present element performs better than the Abaqus S3 element in this test case.…”
Section: Cooks Membranementioning
confidence: 99%
“…Four-node hybrid shell element based on the modified complementary energy functional almost insensitive to mesh distortions was described in [19]. Different methods of incorporating the drilling degree of freedom (DOF) in formulation of the EAS shell elements were compared in [20]. Mixed shell elements with the drilling DOF using the co-rotational kinematics concept were presented in [21][22][23].…”
mentioning
confidence: 99%